1998
DOI: 10.2307/3343538
|View full text |Cite
|
Sign up to set email alerts
|

Violent Crime and Alcohol Availability: Relationships in an Urban Community

Abstract: The relationship between violent crime, neighborhood sociodemographic characteristics, and alcohol outlet densities in Newark, New Jersey is reported, thus extending previous research of municipalities at more refined levels of analysis. Alcohol outlet densities were significant predictors in regression models, but rates of violent crime were better predicted in larger units (R2 = .673 for the census tract level vs. .543 at the census block group level). Alcohol outlet densities, however, were more predictive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
71
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(77 citation statements)
references
References 23 publications
4
71
1
Order By: Relevance
“…Several studies have shown an association between alcohol outlet density and violence (27,58,67). Scribner et al found, for example, that in a typical city in Los Angeles County, 1 alcohol outlet was associated with 3.4 additional violent assault offenses, after adjusting for many confounders including racial/ethnic makeup, age structure, and unemployment.…”
Section: Public Health the Environment And Violent Injurymentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown an association between alcohol outlet density and violence (27,58,67). Scribner et al found, for example, that in a typical city in Los Angeles County, 1 alcohol outlet was associated with 3.4 additional violent assault offenses, after adjusting for many confounders including racial/ethnic makeup, age structure, and unemployment.…”
Section: Public Health the Environment And Violent Injurymentioning
confidence: 99%
“…Using smaller geographical units for analyses in Newark, New Jersey, Speer et al determined that alcohol outlet density was the strongest predictor of violent crime-19% of the variability in violent crime could be explained by alcohol outlet density for census tracts and 28% for census block groups (67). In many of the studies, situational crime prevention, CPTED, broken windows, routine activity, and hot spots theories have been discussed briefly or cited (27,28,58,59,67).…”
Section: Public Health the Environment And Violent Injurymentioning
confidence: 99%
“…Physical, social, and economic availability of alcohol is associated with alcohol consumption among the general population (Parker, Wolz, & Harford, 1978;Rush, Steinberg, & Brook, 1986;Abbey, Scott, Olinsky, Quinn, & Andreski, 1990;Abbey, Scott, & Smith, 1993;Gruenewald, Madden, & Janes, 1992;Gruenewald, Miller, & Treno, 1993) and among young adolescents and older teenagers (O'Malley & Wagenaar, 1991;Wagenaar, 1993;Wagenaar et al, 1996;Jones-Webb et al, 1997). High density of alcohol outlets has been found to be associated with higher rates of alcohol-related health and social problems such as homicide (Scribner, Cohen, Kaplan, & Allen, 1999), assaultive violence (Alaniz, Parker, Gallegos, & Cartmill, 1996;Alaniz, Cartmill, & Parker, 1998;Gorman, Speer, Labouvie, & Subaiya, 1998a;Scribner, MacKinnon, & Dweyer, 1995;Speer, Labouvie, & Ontkush, 1998), domestic violence (Gorman, Labouvie, Speer, & Subaiya, 1998b), traffic safety outcomes (Rabow & Watts, 1982;Jewell & Brown, 1995;Scribner et al, 1994), and mortality, morbidity and economic costs (Tatlow, Clapp, & Hohman, 2000;Mann, Smart, Anglin, & Adlaf, 1991;Rabow & Watts, 1982;Scribner, Cohen, & Farley, 1998;Gorsky, Schwartz, & Dennis, 1988;Smart, Mann, & Suurvali, 1998). Alcohol outlets and advertising appear to be over-concentrated in ethnic minority communities (Alaniz, 2000;Hackbarth, Silvestri, & Cosper, 1995;Altman, Schooler, & Basil, 1991;…”
Section: Introductionmentioning
confidence: 99%
“…They found the risk of having a violent crime on a block rose by 17.6% with every additional bar or tavern. Speer et al 14 (1998) highlight the importance for policy making to recognize the magnitude of alcohol outlet densities' influence on violent crime. Their results showed that a reduction in violence which could be achieved by a 1% decrease in alcohol outlet density would require a 5% increase in median household income or an 8% increase in employment.…”
Section: Introductionmentioning
confidence: 99%